Sustainable food packaging: Factors affecting consumer purchase intention - Li-Yee Chan; Corrinne Mei Jyin Lee (Universitas Internasional Batam, 2023)
Food packaging is the top plastic polluter in the Asia Pacific Region. Therefore, consumer purchase of food in sustainable packaging can reduce the use of plastic. The purpose of this study is to examine the factors that affect consumer purchase intention of sustainable food packaging based on the Theory of Planned Behaviour. The study employed a sample of 200 food consumers. Using multiple regression analysis, the results found (i) attitude, (ii) perceived behavioural control, (iii) environment concern and (iv) electronic word of mouth to be significant antecedents of sustainable food packaging consumer purchase intention. This study enlarges the understanding of the market acceptance of sustainable food packaging.